The Impact of Using TikTok Social Media on the Fifth-Grade Students’ Social Attitudes at SDN 115 Pekanbaru - Nur Azizah; Zaka Hadikusuma Ramadan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the impact of TikTok social media on fifth-grade elementary students’ social attitudes. The method used in the research is qualitative. The data sources are primary and secondary data sources. Primary and secondary data sources involved four teachers, four students, and one school principal who were deemed capable of providing statements and reinforcement for research purposes. Data collection techniques and instruments are interviews, observation, and documentation. Data validity testing uses source and technical triangulation. The triangulation of sources used is related to four teachers, four students, and documents. Technical triangulation is carried out by checking data from the same source with different techniques. The data analysis techniques used are data reduction, data presentation, and conclusions and verification. The conclusion of the research is that the social attitudes of elementary students are going well, even though there are still some students who are not yet optimal in implementing good social attitudes because one of the influences is the use of TikTok social media. The social attitudes of students that teachers have applied to students, either in the classroom or outside the classroom, are being responsible, self-confident, mutual respect, polite, competitive, and honest. TikTok social media has not been used by elementary school students yet, because the TikTok application has more negative impacts if students cannot take positive values from it.